2011
DOI: 10.1002/uog.7764
|View full text |Cite
|
Sign up to set email alerts
|

Persistent right umbilical vein: a prenatal condition worth mentioning?

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 46 publications
4
43
1
6
Order By: Relevance
“…The incidence of 0.40% (48/12,071) detected in the current study seems to be compatible with the reported incidence of RSLT during neonatal ultrasonography (0.08–0.46%)22, 23, 24, 25, 26, 27, 28 and the prevalence of the condition in the adult population 4, 14, 15, 29. To compare and discuss various observations about the anatomy of the liver, clear definitions and knowledge about basic vascular anatomy are required.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of 0.40% (48/12,071) detected in the current study seems to be compatible with the reported incidence of RSLT during neonatal ultrasonography (0.08–0.46%)22, 23, 24, 25, 26, 27, 28 and the prevalence of the condition in the adult population 4, 14, 15, 29. To compare and discuss various observations about the anatomy of the liver, clear definitions and knowledge about basic vascular anatomy are required.…”
Section: Discussionsupporting
confidence: 92%
“…128 Occasionally, the absence of the ductus venosus results in unimpeded placental return because the umbilical vein drains through alternate low-resistance fetal venous pathways, which can lead to significant volume overload and heart failure. 129 The true incidence of fetal venous malformations is undefined, but because of the frequently reported occurrence of cardiac abnormalities, 82 fetal echocardiogram has previously been recommended. Given the existing data, fetal echocardiography may be reasonable to consider in the presence of an umbilical cord or venous abnormality; however, because considerable ascertainment bias may have been introduced in the available studies, usefulness is not well established, especially if obstetric ultrasound is otherwise normal.…”
Section: Abnormalities Of the Umbilical Cord And Venous Systemmentioning
confidence: 99%
“…Il porte sur la présence de varices de la veine ombilicale, d'une duplication de la vésicule biliaire, d'un kyste hépatique ou d'anomalies de trajet de la veine porte ou de ses branches [414].…”
Section: Diagnostic Différentielunclassified
“…Lors du développement, ces veines sont intégrées dans le foie qui est en expansion rapide et forment des anastomoses avec le plexus capillaire hépatique. Trois variantes sont possibles [414] : cette forme, la veine ombilicale s'abouche soit dans les veines iliaques, soit directement dans l'oreillette droite ou la portion adjacente de la veine cave inférieure. La partie extrahépatique des veines ombilicales va régresser rapidement.…”
unclassified
See 1 more Smart Citation